4CPS-205 Enoxaparin dose adjustment in the elderly – the intervention of the clinical pharmacist. (March 2019) - Brito, M; Alcobia, A
Abstract : Background: Enoxaparin dose adjustment in the elderly is essential because its bioaccumulation may cause bleeding events. The high number of elderly protamine administrations in our hospital raised our awareness. The evidence on pharmaceutical interventions (PI) supporting dose adjustment of enoxaparin is almost nonexistent. Purpose: Assessing the need, acceptance and results of PI in the adjustment of enoxaparin doses prescribed to elderly inpatients. Material and methods: Protamine administration retrospective study (January–March 2018) followed by a 2 month prospective longitudinal study (May–June). Prospective study inclusion criteria: inpatients≥65 years (internal medicine ward) on enoxaparin for treatment or thromboprophylaxis with acute kidney injury (AKI) or chronic kidney disease (CKD). Data were collected from electronic patient records. Patients were continuously monitored by calculating creatinine clearance (CrCl) (Cockcroft Gault formula). CrCl <30 ml/min or borderline (30–45 ml/min) led to verbal or electronic PI. Weight adjustments were also considered. The need for protamine use and the occurrence of bleeding events were monitored. Results: In the retrospective study, nine patients (77.9±11.9 years) needed protamine for partial reversal of bleeding events due to enoxaparin, eight of them had CrCl <45 ml/min. In the prospective study were included 35 patients out of 87 (40.2%) (79.9±8.8 years; 54.3% women; 60.0% AKI, 38% CKD; 51.4% on treatment doses, 48.6% on thromboprophylaxis). On average, pharmacists monitored CrCl during 7.4 days out of 9.2 days of treatment. There were 17 PI in 12 patients (75% CKD): seven dose adjustments by CrCl <30 ml/min; six dose adjustments to weight; and four alerts by borderline CrCl. The acceptance rate was 70.6%. The physicians took 1.1 days to electronically adjust the prescribed dose. No protamine was administered during this period. In patients whose PI were accepted, there were not any bleeding events. Major haematomas were observed in two patients whose PI were not accepted. Patients with borderline CrCl presented minor haematomas. Although guidelines indicated dose adjustments only for CrCl <30 ml/min, there is a growing concern about the unadjusted doses' safety in patients with CrCl 30–50 ml/min. Conclusion: PI were relevant in avoiding bleeding events in a growing geriatric population. Collaboration between the clinical pharmacist and medical staff brings improvements in elderly pharmacotherapy. Reference and/or acknowledgements: Shaikh SA, Regal RE. Dosing of enoxaparin in renal impairment. PT 2017;42:245–9. No conflict of interest.